<span>(Y-3)^2 = 4y -12 <=> Y^2 - 6Y + 9 = 4y - 12 <=> 4y = Y^2 - 6Y + 21 <=> y = (Y^2 - 6Y + 21)/4. Solving the equation for y means that we have to express y relative to the other quantities in the equation.</span>
Answer:
The answer is 36
Step-by-step explanation:
1) Add 30 + 2 and get 32
2) Then you just add 32+4 and get 36
Answer:
195
Step-by-step explanation:
Because 36 x 6 = 192 + 3 = 195
Answer:
8
Step-by-step explanation:
100 = x^2 + AC^2
17^2 = AC^2 + (21 - x)^2
289 = AC^2 + 21^2 + x^2 - 2*21*x
289 =<u> AC^2</u> + 441 +<u> x^2</u> - 42x
from 1st equation AC^2 + x^2 = 100
289 = 441 + 100 - 42x
289 = 541 - 42x
42x = 541 - 289 = 252
x = 252/42 = 6
so AC^2 = 100 - 6^2 = 100 - 36 = 64
AC = 8
Answer:
k=88
Step-by-step explanation:
as 8*11=88